USE OF ARTIFICIAL INTELLIGENCE IN THE PUBLIC SECTOR: LEGAL FRAMEWORK AND EXPERIENCES OF THE EU AND THE REPUBLIC OF SERBIA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
Artificial intelligence is slowly becoming a general-purpose technology applicable in all areas of social life.Social existence in a certain territory is determined by the connection of citizens and state institutions, thatis, public exposure and work in favor of the general interest of citizens through various branches of the stateor services known as the public sector. We are thus witnessing the penetration or gradual introduction ofartificial intelligence in the public sector or public administration with the aim of easier servicing andimprovement of the benefits that the state should provide to citizens. The benefits are reflected in therealization of certain rights of citizens as well as in the improvement of economic activities in which citizensand society are very interested.In the paper, we analyze the introduction and use of certain artificial intelligence systems in the public sector,i.e. in its individual parts, we look at its disjointed elements that vary from country to country, attempts toestablish common terms and patterns, and we investigate sensitive and critical areas of public services basedon the taxonomy EU. In this context, the connection between digitization and the creation of eadministration, which potentially includes artificial intelligence systems, is interesting, requiring capacitybuilding and the acquisition of new skills and knowledge for public administration employees. The emphasisin the paper is on the legal framework for their use provided by the EU Regulation on artificial intelligence,especially on the categorization of certain artificial intelligence systems into prohibited and high-risksystems that could be used in the public sector. A special part of the paper is devoted to the assessment ofthe anticipated use of artificial intelligence systems in the public sector in the Republic of Serbia byestablishing a legal framework with soft law norms such as the Strategy for the Development of ArtificialIntelligence in the Republic of Serbia for the period 2020-2025. which was adopted in 2019 and the Ethicalguidelines for the development, implementation and use of reliable and responsible Artificial Intelligencefrom 2023.
Keywords: public sector, public administration, artificial intelligence systems, digitization, taxonomy, public services.